Currency order flow, exchange rate dynamics and market intervention: Empirical evidence from ASEAN-5 foreign exchange markets / Anifowose Abolaji Daniel - Anifowose Abolaji , Daniel (2018)
The microstructure approach in determining exchange rate movements has attracted special attention of academics and practitioners. This approach emphasizes the role of net demand pressure captured by currency order flow in determining exchange rate. This thesis examines the relationship between currency order flow and exchange rate of ASEAN-5 countries namely Indonesia, Malaysia, Philippines, Singapore and Thailand over a 6-year period (2010 – 2015). This study attempts to address three research objectives: (1) To examine the role of currency order flow in determining exchange rates movements against USD(2) To determine the short-run and long-run interaction between micro-macroeconomic variables and exchange rates, and (3) To test the effectiveness of central bank intervention in the foreign exchange markets through the behavior of currency order flow. Therefore, the focus on ASEAN-5 countries is for two reasons; first, these five countries have undergone rapid financial market liberalization, which have made them among the most important markets in the world. Second, these countries mainly practice manage-float exchange rate regime. The aforementioned reason is deemed as an avenue to determine whether the findings and explanations provided in the free-floating exchange rate regime are more widely applicable, or are limited to those markets. Using the portfolio shift model, this illustrates that exchange rates at short horizons are driven by currency order flow. The model of fifteen-minute (high frequency) currency order flow produces R2 statistics between 6 percent (Philippines) and 19 percent (Singapore). These relatively low R2‘s are due to manage-float exchange rate regime practiced by the sample countries. The vector autoregressive model (VAR), vector error correction model (VECM) and forecast error variance decomposition (FEVD) are used to determine the interaction between micro-macroeconomic variables (such as currency order flow, interest rate, country’s risk premium) and exchange rate. The thesis identifies that currency order flow and risk premium of the country are the only two influential determinants of exchange rate for ASEAN-5 countries. To address the final objective of study, the behavior of end-user currency order flow is used to capture the intervention of the central bank in the foreign exchange markets. The findings indicate that the exchange rates of ASEAN-5 countries are sensitive to central bank intervention. The findings also suggest that the central bank intervention will only become effective if the country has a sound monetary and fiscal policy. This thesis is among the first to test simultaneously the behavior of ASEAN-5 countries’ exchange rates using market microstructure approach. Furthermore, this study also examines the exchange rate movements of manage-float exchange rate regime using a dataset of fifteen-minute currency order flow. Therefore, this thesis provides more information to the monetary authorities, market dealers and market players on the importance of employing market microstructure approach to determine exchange rate movements in the emerging markets.